2015
DOI: 10.1021/jacs.5b00877
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Near-Infrared/Blue Mechanofluorochromism of Aminobenzopyranoxanthene

Abstract: Mechanochromic organic molecules (MOMs) that exhibit a large difference of fluorescence wavelength between two states have important potential applications, but few such compounds are known. Here, we report a new MOM, cis-ABPX01(0), which shows switchable near-IR and blue fluorescence responses. Detailed spectrophotometric and single-crystal X-ray analyses revealed that the near-IR fluorescence is attributable to fluorescence from slip-stacked dimeric structures in crystals, while the blue fluorescence is attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(67 citation statements)
references
References 43 publications
(20 reference statements)
0
62
0
1
Order By: Relevance
“…The luminescentp roperties of organicf luorophores in the solid state can be occasionally affected by molecular distributions and morphology.W hen luminescent chromism was induced by mechanical stimuli, such as pressing,c rushing, and grinding,t hese molecules are classified as mechanoluminescent chromic (MLC) compounds. [1][2][3][4][5][6][7] Because of the potential versatility of MLC materials, such as for optical recording/ memory devices, [8] pressure indicators, [9] stress detectors with polymers, [10] and bioprobes for monitoring microenvironmental changes, [11,12] not only the development of MLC compounds, but also modulation of luminescent properties, such as color, intensity,a nd chromism direction,are hot topics with high relevance.H owever,b ecause most conventional luminescent dyes intrinsically show weake mission in the solid state due to aggregation-causedq uenching (ACQ), there are limited numbers of molecular skeletons with clear MLC behavior.I ndeed, it is still challengingt op recisely regulate MLC properties according to preprogrammed design.O ne of the promising candidates to produce MLC compounds with functional tunability is the class of aggregation-inducede mission [13][14][15][16][17][18][19][20] (AIE)-active molecules, which can show bright emission only in the aggregated state. [21] In particular, recent studies reported that vari-ous types of solid-state fluorescent materials with stimuliresponsive fluorescentc hromism involving MLC could be prepared based on the regulation of electronic conjugation through AIE-active organoboron complexes.…”
Section: Introductionmentioning
confidence: 99%
“…The luminescentp roperties of organicf luorophores in the solid state can be occasionally affected by molecular distributions and morphology.W hen luminescent chromism was induced by mechanical stimuli, such as pressing,c rushing, and grinding,t hese molecules are classified as mechanoluminescent chromic (MLC) compounds. [1][2][3][4][5][6][7] Because of the potential versatility of MLC materials, such as for optical recording/ memory devices, [8] pressure indicators, [9] stress detectors with polymers, [10] and bioprobes for monitoring microenvironmental changes, [11,12] not only the development of MLC compounds, but also modulation of luminescent properties, such as color, intensity,a nd chromism direction,are hot topics with high relevance.H owever,b ecause most conventional luminescent dyes intrinsically show weake mission in the solid state due to aggregation-causedq uenching (ACQ), there are limited numbers of molecular skeletons with clear MLC behavior.I ndeed, it is still challengingt op recisely regulate MLC properties according to preprogrammed design.O ne of the promising candidates to produce MLC compounds with functional tunability is the class of aggregation-inducede mission [13][14][15][16][17][18][19][20] (AIE)-active molecules, which can show bright emission only in the aggregated state. [21] In particular, recent studies reported that vari-ous types of solid-state fluorescent materials with stimuliresponsive fluorescentc hromism involving MLC could be prepared based on the regulation of electronic conjugation through AIE-active organoboron complexes.…”
Section: Introductionmentioning
confidence: 99%
“…These emission bands consist of shorter‐wavelength peaks at 350–450 nm and longer‐wavelength broad peaks at 450–650 nm. The intermolecular interactions in the solid state, such as the slip‐stacking dimer formations and the C−H‐π interactions observed by the crystallographic analysis, might account for the red‐shifted, broad fluorescence emissions of furans 1 ,. In solution, such red‐shifted fluorescence bands were not observed even at higher concentrations, ruling out the possibility of aggregate formation in solution, at least at room temperature.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, CÀH···p interactions with 2.466 distance exist between the pairs of dimers, which play ap ivotal role in restricting the intramolecular rotation( Figure 10B2). [26] On the contrary,M PP-d-CN adopted am ore twisted configuration:t he dihedral angles between the central MP ring and the pyridine and BT moieties are 30.158 and 12.638,r espectively ( Figure 9C). Although in MPP-d-CN, the deviation of BT moiety is relatively smaller than that in MPP-d, it should be noted that an additional CNg roup can widen the C=Cb ond moiety,t herebyi ntensifying the deviation, whichc an thus hinder the close contact between the adjacent molecules.…”
Section: Full Papermentioning
confidence: 99%